2018
DOI: 10.1038/s41419-017-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of KRAS-dependent lung cancer cell growth by deltarasin: blockage of autophagy increases its cytotoxicity

Abstract: Deltarasin is a recently identified small molecule that can inhibit KRAS–PDEδ interactions by binding to a hydrophobic pocket on PDEδ, resulting in the impairment of cell growth, KRAS activity, and RAS/RAF signaling in human pancreatic ductal adenocarcinoma cell lines. Since KRAS mutations are the most common oncogene mutations in lung adenocarcinomas, implicated in over 30% of all lung cancer cases, we examined the ability of deltarasin to inhibit KRAS-dependent lung cancer cell growth. Here, for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Deltarasin is a new small molecular inhibitor that suppresses oncogenic KRAS signalling by disrupting the binding of KRAS to its transporter PDEδ, preventing KRAS localizing to endomembranes [4]. Inhibition of mutant KRAS activity, cell growth, and tumour dissemination by deltarasin has been reported in pancreatic cancer, lung cancer and colon cancer [4, 26, 27]. By IF and WB assays, deltarasin had similar effects on MEK/β-TrCP nuclear localization and YAP levels (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Deltarasin is a new small molecular inhibitor that suppresses oncogenic KRAS signalling by disrupting the binding of KRAS to its transporter PDEδ, preventing KRAS localizing to endomembranes [4]. Inhibition of mutant KRAS activity, cell growth, and tumour dissemination by deltarasin has been reported in pancreatic cancer, lung cancer and colon cancer [4, 26, 27]. By IF and WB assays, deltarasin had similar effects on MEK/β-TrCP nuclear localization and YAP levels (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…KRAS is an elusive oncotarget and much effort continues to focus on targeting it by directly inhibiting its function, biogenesis and expression [14,35]. Furthermore, constitutively active KRAS has been linked to increased cell proliferation [36][37][38]. Therefore, we investigated…”
Section: Grifolin Neogrifolin and Confluentin Suppress Kras Expressionmentioning
confidence: 99%
“…32 However, subsequent detailed analysis of the characteristic dose–response curves of deltarasin reveals that this PDEδ ligand displays a ‘switch‐like’ inhibition of proliferation exhibiting cytotoxic effects at concentrations above 9 μM in all tested cell lines, including cancer and normal cells . Our research revealed another limitation of deltarasin, it induces protective autophagy in non‐small cell lung cancer . Additionally, a second inhibitor with similar biochemical potency to deltarasin, deltazinone 1, was rapidly metabolized in in vivo experiments, although it showed a higher binding affinity to PDEδ .…”
Section: Introductionmentioning
confidence: 80%
“…32 Our research revealed another limitation of deltarasin, it induces protective autophagy in non-small cell lung cancer. 33 Additionally, a second inhibitor with similar biochemical potency to deltarasin, deltazinone 1, was rapidly metabolized in in vivo experiments, although it showed a higher binding affinity to PDEδ. 34 Therefore, further challenges of drug discovery and chemical structure optimization will be required to fulfill an unmet medical need.…”
Section: Introductionmentioning
confidence: 99%